Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai di Kantor Camat Pangkalan Kerinci Kabupaten Pelalawan - Ari Nur Wahidah; Maharani Juwita; Ikhwani Ratna (Yayasan Almanar Pujud, 2025)
This research was conducted at the Pangkalan Kerinci District Office, Pelalawan Regency. The purpose of this study was to determine the Influence of Organizational Culture on Employee Performance at the Pangkalan Kerinci District Office, Pelalawan Regency. The population in this study were employees of the Pangkalan Kerinci District Office, Pelalawan Regency. The sample in this study was 37 employees using the Total Sampling technique. The research method used in this study was the saturated sample method (census) in non-probability sampling. Data collection techniques were carried out through questionnaires and interviews. Technical data analysis used Simple Linear Regression Analysis using the SPSS 25 program. Data validity was obtained through validity tests and reliability tests. The results of this study indicate that there is a positive and significant influence of Organizational Culture on Employee Performance. Based on the calculation, the regression Y = 26,000 + 0.392 + e means that every increase in the Organizational Culture variable (X1) will be followed by an increase in employee performance with an R square value of 11.2% while the remaining 88.8% is influenced by other variables not examined in this study.